Minimum Wage: Does It Improve Welfare in Thailand? - Ximena Del Carpio; Julián Messina; Anna Sanz-de-Galdeano (Institute for the Study of Labor (IZA), 2014)
We study the causal impact of the minimum wage on employment and welfare in Thailand using a difference-in-difference approach that relies on exogenous policy variation in minimum wages across provinces. We find that minimum-wage increases have small disemployment effects on female, elderly, and less-educated workers and large positive effects on the wages of prime-age male workers. As such, increases in the minimum wage are associated with increases in household consumption per capita in general, but the consumption increase is greatest among those households around the median of the distribution. In fact, rises in the minimum wage increased inequality in consumption per capita within the bottom half of the distribution.
Keywords: J31; D31; 330; minimum wage; household consumption; poverty; employment; uncovered sector